Pregnancy Outcomes Among Teenagers at a National Referral Hospital in Uganda - Mike Nantamu Kagawa; Otto Alex Owori; Miriam Nakalembe (Hindawi Limited, 2024)
Conclusion: Teenage pregnancy was generally not associated with adverse maternal or fetal outcomes except for preterm birth. The reasons for adverse pregnancy outcomes may reflect a combination of gynecological and biological immaturity, as well as adverse socioeconomic pressures.